The possibility of lapatinib treatment for breast cancer patients with central nervous system metastases.Case study and literature review - Rolski, Janusz; Karczmarek-Borowska, Bożenna; Śmietana, Anetta (Contemporary Oncology/Współczesna Onkologia, 2012)
In patients with breast cancer with overexpression of the HER2 receptor, during treatment with trastuzumab, in 30% of cases brain metastases are observed. The use of lapatinib with capecitabine (L + C) seems to be an efficacious method of curing patients in whom the spread of cancer in this location has occurred. In a patient aged 52 treated by the L + C scheme a stabilization of changes in the brain was noted, lingering for 17 months. The tolerance of the treatment was good. Grade 2 hand-foot syndrome on the NCI 2,0 scale, nausea, a first degree increase in transaminase levels and first degree diarrhea were observed. No hematological or cardiac complications were observed. In the third phase test comparing capecitabine with capecitabine and lapatinib in patients with advanced breast cancer, adding lapatinib to capecitabine significantly prolonged the time until progression and contributed to lessening of the amount of progression of the condition into the central nervous system. Recently published studies showed 6% remission of metastases to the central nervous system in patients with advanced breast cancer with brain metastases treated with lapatinib and 20–21% in patients receiving lapatinib with capecitabine. Future studies evaluating the effectiveness of lapatinib in patients with spread into the central nervous system should include the evaluation of lapatinib in association with cytostatics able to break through the blood-brain barrier. Lapatinib should also be tested in association with brain radiation, considering the results of preclinical studies indicating that it may work as a radiation sensitizer.